Evaluation of heavy metal content in agricultural soil fertilized with chemical fertilizers in the Tasawa Agricultural Project, Libya - Iessa, Kaes Rateb (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2024)
The Tasawa agricultural project was constructed to produce grains in the southern region. The project has employed various chemical fertilizers to enhance agricultural production. However, the use of these fertilizers may lead to the accumulation of heavy metals in the soil. Soil samples taken from the project site showed a mean concentration of Chromium (Cr), Copper (Cu), Cadmium (Cd), Manganese (Mn), Zinc (Zn), Nickel (Ni), and Iron (Fe) at 25.97±11.02, 0.95±0.94, 4.37±3.23, 12.26±7.59, 2.21±2.98, 9.15±10.93, and 267.50±84.96 mg/kg, respectively. The geochemical pollution index (Igeo) shows the non-pollution of Cu, Cd and Zn, while Cr, Mn, Ni, and Fe are unpolluted or slightly polluted. Pearson correlation coefficient indicated a significant positive correlation between Fe-Mn (r=.987**), a significant negative correlation between Mn-Cr (r = -.943**) and a negative correlation between Fe-Cr (r= -.878*).